Response to Letter to the Editor: “Algorithms to Define Abnormal Growth in Children: External Validation and Head-to-Head Comparison” - Chalumeau, Martin; Scherdel, Pauline; Heude, Barbara (The journal of clinical endocrinology and metabolism, 2019)
ORCiD numbers: 0000-0001-8175-3706 (M. Chalumeau); 0000-0003-4517-9430 (P. Scherdel); 0000-0002-1565-1629 (B. Heude).